Conserving Black Grouse Lyrurus tetrix in southern Scotland: evidence for the need to retain large contiguous moorland habitat within a forest-moorland landscape. Issue 4 (2nd October 2019) - Warren, P.; Land, C.; Hesford, N.; Baines, D.
ABSTRACT: Capsule: Black Grouse Lyrurus tetrix in southern Scotland are in severe decline, with remaining birds associated with large contiguous patches of moorland. Aims: To inform Black Grouse conservation programmes in southern Scotland we quantified recent trends in numbers, assessed habitat composition within lek ranges and evaluated the size of suitable habitat patches. Methods: We explored trends in numbers of males at 121 leks surveyed between 1989 and 2018 in southwest and southeast Scotland. Wider surveys of males attending leks between 2006–12 were used to measure habitat composition within lek ranges and to compare with that in the study areas. Numbers of males at leks were considered in relation to habitat types and moorland management categories. Occupancy of moorland habitat patches was explored in relation to their size, connectivity and gamekeeping activity. Results: Abundance at a sample of 121 leks surveyed between 1989–99 and 2017–18 fell from 70 males to zero in the southwest and from 340 to 44 in the southeast, with 82% of leks no longer occupied. Retained leks had more acid and rough grassland (53%) and less conifer cover (6%) within a 1 km radius than extinct leks (32% and 29%) and declines were similar across gamekeeping activity levels. Wider surveys in 2006–12 found acid and rough grassland, and dwarf shrub heath and bog to be the two preferred habitats within lek ranges. Leks were attended by twice as many males where driven Red Grouse Lagopus lagopus scotica shooting was practised. Occupied moorland habitat patches were 26 times larger than unoccupied patches. Conclusion: Black Grouse in southern Scotland are declining across all habitats. Moorland provides important habitat for remaining birds. With government targets to plant more woodland, remaining moorland habitat patches are likely to become more fragmented making them less able to support sustainable connected populations, which may exacerbate declines and enhance risk of regional extinction.